Age and school-segment difference in daily sedentary behavior and physical activity among student (9–23 years): a cross-sectional accelerometer-based survey - Lu, Yijuan; Yu, Kehong; Zhai, Mengjie; Ma, Pan (Frontiers in Pediatrics, 2023)
This study is cross-sectional in nature and aims to investigate and track sedentary behavior (SB) and physical activity among student (aged 9-23 years) for seven consecutive days using an accelerometer. It also intends to analyze the current status of the daily activities of students using age and school-segment differences. The study recruits a total of 384 students (age: 14.41 ± 3.52 years; body mass index [BMI]: 19.66 ± 3.67) from four schools out of which 180 (46.88%) were male. The study uses the means and standard deviations for statistical analysis and independent sample t-tests to determine gender differences. Analysis of covariance is used to determine whether or not daily SB and physical activity were statistically significant students according to gender and school segment followed by LSD post-hoc tests for multiple comparisons. The results demonstrate that students were less physically active (moderate-to vigorous-intensity physical activity [MVPA]:60.4 ± 23.48 min/d) and more sedentary (598.47 ± 162.63 min/d). The sedentary time of the students displays an inverted U-trend, and their participation in MVPA exhibits a W-shape. After controlling for BMI, the results of ANCOVA point to a significant school-segment effect (p < 0.001) for SB (F = 83, ηp2 = 0.4) and physical activity (lowintensity physical activity: F = 108.61, ηp2 = 0.47; MPA: F = 401.65, ηp2 = 0.76; high-intensity physical activity: F = 88.43, ηp2 = 0.42; MVPA: F = 118.42, ηp2 = 0.49). Based on the behavioral characteristics of students across school segments, this study concluded that interventions targeting students' physical activity and physical health should be school segment specific. The results of the study provide a basis for future analysis of factors influencing students' physical activity behaviors across school segments and for proposing targeted intervention strategies for the future.